Some Results via Gril Semi –p-Open Set - B., Esmaeel R.; M., Shahadhuh N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
The significance of the work is to introduce the new class of open sets, which is said Ǥ- -open set with some of properties. Then clarify how to calculate the boundary area for these sets using the upper and lower approximation and obtain the best accuracy.